G Protein-Coupled Estrogen Receptor: Rapid Effects on Hippocampal-Dependent Spatial Memory and Synaptic Plasticity - Ashok Kumar; Thomas C. Foster (Frontiers in Endocrinology, 2020)
In the hippocampus, estrogen regulates gene transcription linked to neuronal growth, neuroprotection, and the maintenance of memory function (1–3). The mechanism is likely to involve genomic regulation through classic estrogen receptor (ER) signaling cascades that influence transcription. Estrogens binding to classic nuclear ERs, alpha (ERα) and beta (ERβ), and have pleotropic effects on development, behavior, and neurophysiological functions, including synaptic plasticity and memory consolidation (4–7). In addition to ERα and ERβ, estrogen can also initiate activation of classical second messenger signaling cascades to influence the activity of G-proteins and a host of kinases, resulting in rapid changes in physiology (8–14). These rapid effects of estrogen are commonly mediated by membrane receptors. In the late 90s, multiple laboratories cloned cDNA/gene for an orphan G-protein-coupled receptor with very low homology with other G-protein-coupled receptors and named it G-protein-coupled receptor 30 (GPR30) (15–20). Later in 2007, the International Union of Basic and Clinical Pharmacology designated GPR30 as G protein-coupled estrogen receptor (GPER) (21); GPER is a seven-transmembrane G-protein-coupled receptor, predominantly expressed on the cell membrane (22). Interestingly, GPER is reported to mediate many of the rapid responses of estradiol in the adult brain, and is widely distributed in the mammalian brain including the plasma membrane of hippocampal neurons (23–31). GPER modulates second messenger signaling cascades involving Gαs- and Gαi/o-associated increase in cyclic adenosine monophosphate and phosphoinositide 3-kinase or Src protein kinase respectively (32, 33). Activation of GPER is also associated with phospholipase C, and the inositol receptor and ryanodine receptor-mediated increase in intracellular calcium (24, 34). This commentary is concentrated specifically on the possible rapid effects of GPER in hippocampal-dependent spatial memory function and synaptic plasticity.